Impact of respiratory syncytial virus on Streptococcus pneumoniae resistance to β-lactam antibiotics: an investigative study in children - Lu Li; Yushun Wan; Yuncheng Wang; Ye Tao; Xiao Long; Enmei Liu; Yu Deng (BMC Microbiology)
Abstract Background This study characterizes the molecular interplay between respiratory syncytial virus (RSV) glycoproteins (G/F) and Streptococcus pneumoniae (S.pn) penicillin-binding proteins (PBPs), while evaluating RSV’s potential role in modulating S.pn β-lactam resistance. Methods Protein docking and pull-down assays assessed G/F-PBP interactions. In vitro RSV-S.pn co-culture experiments evaluated β-lactam susceptibility (MIC determination). We retrospectively analyzed 2012–2021 antimicrobial resistance data from 1-59-month-old community-acquired pneumonia patients at Chongqing Medical University Children’s Hospital with confirmed S.pn and/or RSV nasopharyngeal carriage. Results Computational modeling revealed low G/F-PBP binding affinity (iPTM < 0.6), corroborated by absent PBP1a interaction in pull-down assays. RSV exposure did not alter S.pn β-lactam MICs (penicillin/amoxicillin ≤ 2 µg/mL; cefepime/cefotaxime ≤ 1 µg/mL; meropenem ≤ 0.25 µg/mL). Retrospective data showed elevated penicillin resistance in RSV + S.pn co-detections vs. S.pn alone during 2012 (2.8% vs. 40.9%), 2017 (2.8% vs. 30.4%), and 2018 (6.2% vs. 38.6%) (all p < 0.001). No RSV-associated resistance increases occurred for amoxicillin, cephalosporins, or meropenem. Conclusions RSV demonstrates negligible impact on S.pn β-lactam resistance mechanisms, elevated resistance rates to amoxicillin and cephalosporins necessitate enhanced antimicrobial stewardship through diagnostic-guided prescribing and resistance surveillance to optimize β-lactam efficacy in pediatric care.